A bibliometric outlook of the most cited documents in business, management and accounting in Ibero-America (2020)
Research on business, management and accounting (BMA) in the past century has been overwhelming. Regardless of its significance, regions such as Ibero-America have been overlooked from exhaustive studies on bibliometrics in the subject of BMA. Here, a bibliometric outlook of the subject of BMA in Ibero-America using 19 variables was conducted by analyzing the ten most cited documents in BMA in each country from 1996 to 2017 using the citation database Scopus. The main findings showed a rapid increase in intellectual production led by Spain and Portugal, which also constitute most of the citations. The majority of the most cited studies are behind paywalls. Institutional status (i.e., private or public) has a significant effect on AACSB accreditation. A negative concern that arises for the whole region, mainly Latin-America, is the discriminated use of a journal with predatory features. © 2019 AEDEM